Health Service Readiness, Availability, and Utilization of Primary Health Care Facilities for Non-Communicable Diseases in Shan State, Myanmar - Aung, Win Htike; Kitreerawutiwong, Nithra; Keeratisiroj, Orawan; Jariya, Wutthichai (Iranian journal of public health, 2022)
Background: Non-communicable diseases (NCDs) are increasing in Myanmar. There have been limited studies to assess the health service system for NCDs patients at the primary health care (PHC) level. We aimed to assess and compare the health service readiness, availability, and utilization of PHC facilities for NCDs in districts in Myanmar. Methods: This cross-sectional study collected data by questionnaires from 242 health care providers working at PHC facilities in three districts in Shan State, Myanmar from January 2020 to January 2021. Differences were calculated with the ANOVA test for NCD capacity readiness and NCD service availability and the Kruskal-Wallis test for NCD service utilization. Results: PHC facilities had a mean score of greater than 70% for NCD capacity readiness of health workforces, health information systems, and essential medicines and equipment domains, but there were large gaps for improvement in financing and governance of health. Almost all PHC facilities had NCD services available, and the differences were not significant among the three districts. However, the mean scores of NCD services availability for chronic respiratory diseases and cancers were lower in all districts. Regarding NCD service utilization, the screening and new patient rates had significant differences among districts (P-value < 0.05). Conclusion: We revealed the situation and gaps in managing NCDs in Myanmar’s PHC facilities. These findings can inform policymakers at the state and district levels to implement programs for improving health services for NCDs, particularly in rural areas.